2015
DOI: 10.4103/0971-5916.154509
|View full text |Cite
|
Sign up to set email alerts
|

Sudarshan Kriya yoga improves quality of life in healthy people living with HIV (PLHIV): results from an open label randomized clinical trial

Abstract: Background & objectives:Improving quality of life (QOL) of healthy people living with HIV (PLHIV) is critical needing home-based, long-term strategy. Sudarshan Kriya yoga (SKY) intervention is acknowledged for its positive impact on health. It is hypothesised that SKY would improve PLHIV's QOL, justifying an evaluation.Methods:In this open label randomized controlled pilot trial, 61 adult PLHIV with CD4 count more than 400 cells/µl and Karnofsky scale score above 70 were enrolled. Those with cardiac disease, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The yoga group showed improved quality of life and better scores on the perceived stress scale and the impact of events scale, although their cortisol levels did not change. And in the other quality of life study, yoga was compared with standard care [115]. The yoga group trained for six days to prepare for daily practice at home (30 min sessions).…”
Section: Hivmentioning
confidence: 99%
“…The yoga group showed improved quality of life and better scores on the perceived stress scale and the impact of events scale, although their cortisol levels did not change. And in the other quality of life study, yoga was compared with standard care [115]. The yoga group trained for six days to prepare for daily practice at home (30 min sessions).…”
Section: Hivmentioning
confidence: 99%
“…intervention compared to controls.24 However, the intervention did not include a physical activity component, and PLWH taking antiretrovirals were excluded from the study. 24 An RCT with a 1-month integrated yoga intervention conducted with male (n = 24) and female (n = 20) PLWH showed a significant reduction in depression scores among yoga participants compared to controls.25 A metaanalysis of 7 RCTs conducted with PLWH determined that yoga interventions resulted in large improvements in perceived stress, positive affect, and anxiety compared to controls. 26 Finally, a systematic scoping review of 84 studies showed that mindfulness, relaxation techniques, cognitivebehavioral strategies, and yoga had beneficial effects on health-related quality of life and physical and psychological symptoms among PLWH.…”
mentioning
confidence: 99%
“…We identified 11 papers, including 8 articles and 3 conference abstracts, that described 9 studies assessing the effects of yoga on people living with HIV [20, 3542]. Five studies used a RCT design [20, 3841], one had a RCT pilot design [42], and three [3537] a one-group pretest-posttest design (Table 4). Two studies [36, 38] collected qualitative data to explore the participants’ perspective on the yoga’s effect on their wellbeing.…”
Section: Resultsmentioning
confidence: 99%